2009
DOI: 10.1111/j.1365-2664.2009.01687.x
|View full text |Cite
|
Sign up to set email alerts
|

Resolving the conflict between driven‐grouse shooting and conservation of hen harriers

Abstract: Summary 1.  Birds of prey and driven‐grouse shooting are at the centre of a long‐standing human–wildlife conflict. Hen harrier predation can reduce grouse shooting bags, limit grouse populations and cause economic losses. Despite legal protection, hen harrier numbers are severely depleted on driven‐grouse moors. 2.  In limited trials, provision of supplementary food to hen harriers greatly reduced their predatory impact on young grouse, but did not result in higher grouse densities for shooting. Consequently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 19 publications
(41 reference statements)
1
41
1
Order By: Relevance
“…In this predator conflict, these elements are starting to come into place after several decades and possible solutions are currently being debated and explored in the field (see Anderson et al 2009;Redpath and Thirgood 2009;Sotherton et al 2009;Thirgood and Redpath 2008;Thompson et al 2009). There will need to be flexibility and compromise.…”
Section: Examples Of Biodiversity Conflictsmentioning
confidence: 98%
“…In this predator conflict, these elements are starting to come into place after several decades and possible solutions are currently being debated and explored in the field (see Anderson et al 2009;Redpath and Thirgood 2009;Sotherton et al 2009;Thirgood and Redpath 2008;Thompson et al 2009). There will need to be flexibility and compromise.…”
Section: Examples Of Biodiversity Conflictsmentioning
confidence: 98%
“…Social acceptance of management strategies was noted in several papers as being an important objective (Witmer et al 2000;Andreassen et al 2005;Massei et al 2011), with one paper stating that the public have a right to involvement in conservation decision making due to the amount of public funding used for this purpose (Thompson et al 2009). However, only one study reported that public acceptance had been actively sought in the long term (Ziegltrum 2006) and none of the papers explicitly examined the level of public acceptance in diversionary feeding.…”
Section: Have Conservation Conflicts Been Reduced?mentioning
confidence: 99%
“…To reach this optimal win-win situation, more work on the perceptions about predators and wildlife at large among managers and conservationists should be developed to look for common ground, and more work about quantifying the economic losses to predation (in comparison with economic investments on predator control) should be developed, as quantification may help influencing perceptions. Beyond that, game managers should stop using illegal and nonselective control methods in order to modify the perception of nonhunters that the use of illegal methods is widespread (Thompson et al 2009). On the other hand, ecological scientists should boost the ongoing process of evaluation of the selectivity of predator control methods (Muñoz-Igualada et al 2008, Díaz-Ruíz et al 2010, should encourage the development of sound experimental research on alternative selective methods that are viewed as effective by managers, and should continue work on the effects of predation on population ecology of red-legged partridge, and other game and nongame prey.…”
Section: Conclusion and The Way Forwardmentioning
confidence: 99%